SINTESIS GEOPOLIMER BERBAHAN DASAR LEMPUNG LATERITE DENGAN PENAMBAHAN ZnO SEBAGAI KOMPOSIT FUNGSIONAL - Zulkifli, Muhammad; Subaer, Subaer; Nurhayati, Nurhayati (Universitas Negeri Makassar, 2019)
The main purpose of this research is to study the microstructure and thermal properties of geopolymers by adding ZnO as a functional composite. Functional composite materials synthesized by alkali activation, using metalempung as the base material and ZnO as aggregate. ZnO was synthesized from ZnSO4 using the precipitation method. The addition of ZnO mass in geopolymer paste was varied from 0.10g; 0.20g; and 0.30g. X-Ray Difraction (XRD) was used to determine the phase formed in functional composite material. The thermal characteristic of the samples was examined by means of Differential Scanning Calorimetry (DSC). The results showed that the composition of ZnO did have a significant effect on changes in microstructure sample. Functional composite materials also had entalphy change and exsoterm peak smaller than sample geopolymer